Effects of dietary camelina, flaxseed, and canola oil supplementation on inflammatory and oxidative markers, transepidermal water loss, and coat quality in healthy adult dogs - Richards, Taylor L.; Burron, Scarlett; Ma, David W. L.; Pearson, Wendy; Trevizan, Luciano; Minikhiem, Debbie; Grant, Caitlin; Patterson, Keely; Shoveller, Anna K. (Frontiers in Veterinary Science, 2023)
Camelina oil contains a greater concentration of omega-3 (n-3) α-linolenic acid (C18:3n-3; ALA) than omega-6 (n-6) linoleic acid (C18:2n-6; LA), in comparison to alternative fat sources commonly used to formulate canine diets. Omega-3 FAs are frequently used to support canine skin and coat health claims and reduce inflammation and oxidative stress; however, there is a lack of research investigating camelina oil supplementation and its effects on these applications in dogs. The objective of this study was to evaluate the effects of camelina oil supplementation on coat quality, skin barrier function, and circulating inflammatory and oxidative marker concentrations. Thirty healthy (17 females; 13 males; 7.2±3.1 years old; 27.4±14.0 kg body weight (BW)) privately-owned dogs of various breeds were used. After a 4-week wash-in period consuming sunflower oil (n6:n3=1:0) and a commercial kibble, dogs were blocked by age, breed, and size, and randomly assigned to one of three treatment oils: camelina (n6:n3=1:1.18), canola (n6:n3=1:0.59), flaxseed (n6:n3=1:4.19) (inclusion level: 8.2g oil/100g of total food intake) in a randomized complete block design. Transepidermal water loss (TEWL) was measured using a VapoMeter on the pinna, paw pad, and inner leg. Fasted blood samples were collected to measure serum inflammatory and oxidative marker concentrations using enzyme-linked immunosorbent assay (ELISA) kits and spectrophotometric assays. A 5-point-Likert scale was used to assess coat characteristics. All data were collected on weeks 0, 2, 4, 10, and 16 and analyzed using PROC GLIMMIX in SAS. No significant changes occurred in TEWL, or inflammatory and oxidative marker concentrations among treatments, across weeks, or for treatment by week interactions. Softness, shine, softness uniformity, color intensity, and follicle density of the coat increased from baseline in all treatment groups (P < 0.05). Outcomes did not differ (P > 0.05) among treatment groups over 16-weeks, indicating that camelina oil is comparable to existing plant-based canine oil supplements, flaxseed, and canola, at supporting skin and coat health and inflammation in dogs. Future research employing an immune or exercise challenge is warranted, as the dogs in this study were not subjected to either.